Harnessing Major Nectar Bearing Forest Plants in some Potential Regions of Ethiopia-an overview of Observations for Profitable Beekeeping - Thakur, A. K.; Kandari, L. S. (Indian Forester, 2015)
In Ethiopia, forests play an important role in enhancing household livelihood of residing rural communities besides maintaining ecological balance. More than 50% of the bee colonies are active in the forest areas where different trees, shrubs and herbs are to be found growing, having variable flowering period thereby providing a source for five races of honeybees for collecting nectar and pollens. It is because of the presence of diversified trees that forests remain a source of assured honey when compared to crops in cultivated areas. Out of total 40 major trees present in the forest, seven of them like Erica arboreal, Eucalyptus spp, Euphorbis candelabrum, Diospyros mespeliformis, Piliostigma thonningii, Azadirachta indica and Dracaena afromontana are reported to be exclusively source of nectar. Trees like Schinus molle hold promise as a major source of pollen. Out of a total 30 herbs and shrubs, herbs plants like Bidens spp., Guizotia scabra, Hypoestes forskalii and Agave sisalana are assured source of nectar while four shrubs i.e. Hypericum revolutum, Plantago lanceola, Solanum nigrum and Rumex nervosus are abundant source of pollen to meet the protein requirements of honey bees.